Instructor Impact on Differences in Teaching Presence Scores in Online Courses - Fiock, Holly; Maeda, Yukiko; Richardson, Jennifer C. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
Using three interdependent constructs: social, cognitive, and teaching presence, the Community of Inquiry framework is a theoretical process model of online learning. Specifically, teaching presence contains three sub-elements—(a) facilitation of discourse, (b) direct instruction, and (c) instructional design and organization—that work together to create a collaborative-constructivist learning environment. Data from the Community of Inquiry survey from 160 learners in 11 course sections were analyzed using a one-way analysis of variance (ANOVA) to determine whether statistically significant differences existed in teaching presence scores between sections of two online courses with identical course design taught by different instructors. Results showed significant differences between individual instructors’ teaching presence scores for each of the two courses. Specifically, significant differences were found in each sub-element of teaching presence except for one course’s instructional design and organization. Conceptual and methodological explanations of the findings are provided, and implications and suggestions for future research are discussed.